(untitled) (Research, Society and Development, 2021)
The aim of this study was to analyze the prevalence of Work-Related Musculoskeletal Disorders (WMSD) in university restaurant workers. This is a cross-sectional and descriptive study with workers from four university restaurants in Belo Horizonte/MG. WMSD assessment in the last twelve months was investigated using the Nordic Musculoskeletal Symptoms Questionnaire (QNSO), composed of closed questions and organized by thematic sets that included demographic, socio-familial, health self-assessment, anthropometric variables, occupational characteristics and musculoskeletal symptoms. self-reported. Data were tabulated and analyzed by SPSS (p<0.05). 87 workers participated in the research (72.5% of the sample), with a mean age of 37 ± 9.8 years, 81% female, mean working time of 9.3 ± 7.5 years, and working hours 40 hours per week. Regarding the presence of WMSD in the last twelve months, pain in the shoulder (47.1%), lower back (40.2%), ankles/feet (39.1%), and temporal region (37.1%) prevailed.). There was a prevalence of musculoskeletal symptoms associated with posture, depression, working hours and training courses. It is concluded that attention should be directed to the attitudes adopted by restaurant workers when performing tasks in order to reduce the incidence of occupational diseases.